Pengaruh Penggunaan Media Flip Book Dalam Meningkatkan Minat Belajar Bahasa Indonesia Siswa Kelas V SD Inpres Samata Kecamatan Somba Opu Kabupaten Gowa - Fatima Fatima; Aliem Bahri; Maria Ulviani (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The purpose of this study was to determine the effect of using flip book media in increasing interest in learning Indonesian for class V SD Inpres Samata, Somba Opu District, Gowa Regency. This type of research is Pre-Experimental Design research. The sample in this study were 19 students. Data collection techniques were carried out using questionnaires, learning achievement tests and observation sheets. The data analysis technique in this study is a descriptive data analysis technique and the T-Test.The results showed that (1) students' interest in learning Indonesian before the implementation of flip book media was generally in the less interested category and student learning outcomes were in the pretest with an average score of 45.7. (2) Student interest in learning Indonesian after the implementation of the flip book media increased to an interested category and student learning outcomes in the posttest with an average score of 86.8. (3) The results of the t-test analysis regarding the effect of flip book media on both interest and learning outcomes of student participants showed that the significance value obtained was good for the first hypothesis, namely the effect of flip book media on learning interest (Sig = 0.000) and the second hypothesis, namely the effect of flip book media on learning outcomes (Sig = 0.011) is smaller than the assigned alpha value of 0.05 (0.000 <0.05 and 0.011 <0.05). Based on the results of the research that has been done, it is concluded that flip book media has an effect on increasing interest and learning outcomes of Indonesian in class V students of SD Inpres Samata, Somba Opu District, Gowa Regency.